2017
DOI: 10.3389/fphys.2017.01023
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electronic Cigarette (ECIG)-Generated Aerosol and Conventional Cigarette Smoke on the Mucociliary Transport Velocity (MTV) Using the Bullfrog (R. catesbiana) Palate Paradigm

Abstract: Background: While ECIGs are under scrutiny concerning safety, particularly in reference to the physiological impact that aerosolized ECIG liquid (E-liquid) may have on respiratory tissues, others believe that ECIGs are a “Harm Reduction” alternative to conventional cigarettes. Previous studies investigating ciliated respiratory epithelium indicate that smoking shortens cilia length, reduces cilia beat frequency and disrupts respiratory epithelium, which most likely contributes to the inhibition of mucocilliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…20,33,34 Other studies also showed that chronic exposure to cigarette smoke stimulates the parasymphatethic nervous system (glandular hypersecretion and vasodilatation), inhibits secretion of Cl À and Kþ conductance in normal respiratory epithelium cells, alters epithelial salts and water transport, alters morphology of the epithelium in the entire of respiratory tract (metaplasia with keratinisation), reduces cells viability, and induces cell apoptosis (opposite mitogenic effect or proapoptotis depending on the concentration of smoke and impairment of cell regeneration in respiratory epithelium), induces matrix metaloproteinases (zinc dependent endopeptidase) that relates to the loss of NMC function and the epithelial disruption exposed to smoke via direct cell-to-cell or cell-to-basement membrane connections, and increases protein kinase-C (PKC) activity related to inhibitory effect on CBF. 7,30,[35][36][37] Proença M (2011) reported that the NMC value in smokers was insignificantly higher immediately after smoking and significantly higher than in non-smokers 8 hours after smoking. The difference between them may be an effect of nicotine on the sympathetic nervous system, which accelerates CBF.…”
Section: Discussion Nasal Mucociliary Clearance In Smokersmentioning
confidence: 99%
See 1 more Smart Citation
“…20,33,34 Other studies also showed that chronic exposure to cigarette smoke stimulates the parasymphatethic nervous system (glandular hypersecretion and vasodilatation), inhibits secretion of Cl À and Kþ conductance in normal respiratory epithelium cells, alters epithelial salts and water transport, alters morphology of the epithelium in the entire of respiratory tract (metaplasia with keratinisation), reduces cells viability, and induces cell apoptosis (opposite mitogenic effect or proapoptotis depending on the concentration of smoke and impairment of cell regeneration in respiratory epithelium), induces matrix metaloproteinases (zinc dependent endopeptidase) that relates to the loss of NMC function and the epithelial disruption exposed to smoke via direct cell-to-cell or cell-to-basement membrane connections, and increases protein kinase-C (PKC) activity related to inhibitory effect on CBF. 7,30,[35][36][37] Proença M (2011) reported that the NMC value in smokers was insignificantly higher immediately after smoking and significantly higher than in non-smokers 8 hours after smoking. The difference between them may be an effect of nicotine on the sympathetic nervous system, which accelerates CBF.…”
Section: Discussion Nasal Mucociliary Clearance In Smokersmentioning
confidence: 99%
“…6,47 Other studies also reported that formaldehyde in ECIG-generated aerosols related to DNA strand breaks and cell death and propylene glycol thicken the respiratory epithelium by increasing the number of goblet cells and increasing the content of mucin within the goblet cell. 6,36 Strength and Limitation of the Study…”
Section: Xavier Et Al 2013 20mentioning
confidence: 99%
“…In addition to the formation of harmful acetals, humectants, when heated by an ENDS device, have been shown to form toxic carbonyl compounds [40][41][42][43][44][45], some of which, including formaldehyde, are carcinogenic and have been suggested to play a role in several respiratory diseases commonly seen in cigarette smokers [45,46]. Another concern is that base ingredients of e-cig liquids (PG, VG) could be respiratory irritants and be harmful to the lungs, leading to airway obstruction and inflammation [47,48]. While benzoic acid is often used as a food preservative, in inhalable form, it is a well-known respiratory irritant that can cause coughing and sore throat if exposure continues [49].…”
mentioning
confidence: 99%
“…Age-synchronized L4 larvae on NGM agar plates containing food were placed into clear cylindrical acrylic exposure chambers uncovered and exposed to 30 puffs air (control), ECIG-generated aerosol, or conventional cigarette smoke. Air, ECIG aerosol, or smoke was pumped into the exposure chambers similar to that previously described ( Palazzolo et al, 2017b ). Briefly, two Cole-Parmer Master Flex L/S peristaltic pumps (Vernon Hills, IL, United States) were used to simulate puffing on Triple 3 (Kennesaw, GA, United States) eGo style ECIG device or conventional Marlboro (84 mm, full strength) cigarettes.…”
Section: Methodsmentioning
confidence: 99%